2012
DOI: 10.1111/j.1365-2966.2012.20718.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical abundances of magnetic and non-magnetic Herbig Ae/Be stars

Abstract: The photospheres of about 10–20 per cent of main‐sequence A‐ and B‐type stars exhibit a wide range of chemical peculiarities, often associated with the presence of a magnetic field. It is not exactly known at which stage of stellar evolution these chemical peculiarities develop. To investigate this issue, in this paper we study the photospheric compositions of a sample of Herbig Ae and Be stars, which are considered to be the pre‐main‐sequence progenitors of A and B stars. We have performed a detailed abundanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
173
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(189 citation statements)
references
References 73 publications
15
173
1
Order By: Relevance
“…Second, early-type stars with metal-poor photospheres, in particular the λBoo stars, show an ultraviolet excess (Murphy & Paunzen 2017). Folsom et al (2012) and Kama et al (2015) found a relatively high fraction of HAeBes in their samples (up to ∼50%) showing the λBoo pattern to varying degrees. If this effect is common among the targets in our sample, it is possible that M  has been systematically overestimated.…”
Section: Appendix a Scattered-light Disk Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Second, early-type stars with metal-poor photospheres, in particular the λBoo stars, show an ultraviolet excess (Murphy & Paunzen 2017). Folsom et al (2012) and Kama et al (2015) found a relatively high fraction of HAeBes in their samples (up to ∼50%) showing the λBoo pattern to varying degrees. If this effect is common among the targets in our sample, it is possible that M  has been systematically overestimated.…”
Section: Appendix a Scattered-light Disk Samplementioning
confidence: 99%
“…The SED only reveals an infrared excess longward of 20 μm, leading them to conclude that this is a Vega-type system. Folsom et al (2012) included this source in their survey of abundances among Herbig Ae/Be stars, noted the lack of strong optical emission lines, and found that the star had a solar abundance pattern (see also Fossati et al 2009). We infer the luminosity for this source from the published photometry (Høg et al 2000), adopting the distance from Gaia Collaboration et al (2016), and we arrive at L å =87 L ☉ .…”
Section: Appendix D Comment On Individual Systemsmentioning
confidence: 99%
“…We adopt the photospheric abundances from Acke & Waelkens (2004) and Folsom et al (2012). For overlapping sources, the surveys are largely consistent, but we adopt the Folsom et al values as the study is more consistent in the stellar parameter determination.…”
Section: The Elemental Abundancesmentioning
confidence: 99%
“…The abundances for HD 100546 are from Kama et al (2015) and for HD 34282 from Merín et al (2004). HD 101412 was identified as a λ Boö star by Cowley et al (2010), we use newer abundances from Folsom et al (2012). The solar abundances shown in Fig.…”
Section: The Elemental Abundancesmentioning
confidence: 99%
See 1 more Smart Citation